MANAJEMEN MEDIA PEMBELAJARAN DALAM PENDIDIKAN IPA: HUBUNGAN ANTARA PREFERENSI SISWA DENGAN KOMPETENSI DAN MOTIVASI BELAJAR - Fadillah, Muhammad Aizri; Festiyed; Usmeldi; Lufri; Mawardi; Tanjung, Yul Ifda (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
The use of learning media in science education is increasingly important to improve students' learning competence and motivation, yet there is still a gap in the understanding of the effectiveness of strategic media management. This study aims to explore the role of learning media management in improving students' competencies as well as understanding the influence of students' preferences for learning media on their learning motivation. This study used a quantitative design with a survey method. The sample consisted of 54 junior high school students in North Sumatra Province who were selected using the convenience sampling method. Data were collected through an online survey covering four main constructs: teachers' learning media management strategies, students' science competencies, students' preferences for learning media, and students' learning motivation. Data analysis was conducted using SmartPLS (V.4) software to test the validity and reliability of the research instruments and SPSS (V.26) to analyze the relationship between variables through multiple regression analysis (univariate; ENTER model). The results showed that effective management of learning media, especially in visualizing complex concepts, had a significant influence on improving the procedural aspects of students' competence, although the influence on conceptual understanding was still limited. In addition, students' preference for relevant, engaging, and contextualized media was shown to positively influence their motivation, especially in the aspects of active engagement and learning comfort. These findings highlight the importance of interactive and strategic media design and the need for teacher training in maximizing the use of learning media. The implications of this study include the development of educational policies that support the integration of student preference-based learning media and the increase of teachers' capacity to manage media effectively to improve student learning outcomes.